(untitled) (Research, Society and Development, 2022)
The present research aims to investigate in a bibliographical way, the comprehensive description of the theme, regarding an interdisciplinary proposal for meaningful learning in elementary school. In this way, the present research was directed with the objective of analyzing and understanding how the proposal of interdisciplinary practices in elementary education that enable the construction of meaningful learning has been addressed in scientific research and academic productions. The research sought to analyze the possibilities of this teaching format in publications presented through dissertations published in the Digital Library of Theses and Dissertations (BDTD), between the years 2011 and 2021. From the keywords: meaningful learning, interdisciplinarity, elementary education. At the end, 8 dissertations that met the inclusion and exclusion criteria defined a priori were analyzed. Data analysis was performed based on the theoretical assumptions of Bardin’s Content Analysis. As a result, it was observed that it is necessary that the methodological organization adopted in elementary school is made in order to understand and describe the educational process and its methodological form of learning, but that the topic has been little addressed in academic research in recent years, making it necessary to rethink the proposal as necessary for the quality of the teaching-learning process.